Advanced teaching methods for the technology classroom - Petrina, Stephen (Hershey, PA : Information Science Pub., 2007)
"This book provides a comprehensive, critical approach to meeting the new challenges of technology in the classroom. It gathers together research on technology methods, principles, and content, acting as a reference source for proven and innovative methods. It presents an introduction to teaching educational technology, design, and engineering, and contains strategies for innovation in technology education"--Provided by publisher.
Ηλεκτρονικό βιβλίο
Keywords: Technical education; Technology -- Study and teaching; Electronic books